Similarities and differences between hulled and dehulled kernels of spelt wheat (Triticum spelta L.) - Ugrenović Vladan; Glamočlija Đorđe; Filipović Vladimir; Vučković Jovana (Selekcija i Semenarstvo, 2012)
Both types of spelt wheat kernel, hulled and dehulled, can be used for sowing. Researchers still argue about which one of those types is more appropriate. The goal of this work was to contribute to better understanding of spelt wheat kernels’ use, which were differently processed in variable agroecological settings. Dynamics of water acquisition is the same for both hulled and dehulled kernels of spelt wheat, but the difference in water content required for germination leads to different times of this process. Negative influence of hulled kernels on germination is amplified in periods of drought and unfavorable temperatures. On the other hand, the advantage of the hulled spelt wheat kernels’ use in organic production is in its better protection from pathogenic fungi. It has been observed that the growth rate and the coleoptile length were higher in spelt wheat comparing to the common wheat. Also, spelt wheat showed much higher tolerance to lower oxygen inflow (hypoxia) in the stressful conditions of very humid and cold soil. Fast coleoptile growth led to faster germination of spelt wheat and reduced duration of hypoxia. These traits facilitate the germination of spelt wheat kernels which are firmly enveloped with hulls. Our present experience with differently processed spelt wheat kernels indicate the advantages of dehulled and disinfected seeds. But also, hulled kernels could improve its quality by additional processing.